Acquired syphilis in childhood: clinical study, diagnosis laboratory and sexually abuse - Carvalho, Altamiro Viana e Vilhena de; Passos, Mauro R.L.; Oliveira, Leidy H.S.; Lopes, Vania G.S.; Herdy, Desmar V.H.; Pinheiro, Vandira M.S. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Syphilis is one of the most frequent sexually transmitted diseases find in brazilian population in spite o f the new drugs and the modem diagnostic techniques. lt is also known that children also are victims of these diseases. Sexually Abused Children attended at Sexually Transmitted Disease Sector in Unversidade Federal Fluminense from 1987 to 1996 had their files reviewed, looking for those presenting acquired syphilis. Clinical and laboratory findings are described and compared with other authors findings, using lndex Medicus review for the last 25 years, and internet data basis . We also alert health workers about the importance of dfagnosis and tre-atment of this pathology. Only 3 patients were attended, and the most commonly found lesions were condylomata lata (100%) and regional linphadenopathy. ln reviewed bibliograpby, were also frequent presence of chancre and assimptomatyc patients. We also presents importance of knowing legal implications in attending a sexually abused children and recommended procedures. Positive syphilis se-rology occurs and positive history for sexual abu se were present in ali patients.